Metoda określania syntetycznego wskaźnika efektów gospodarowania zasobami przyrodniczymi, ludzkimi i ekonomicznymi nadleśnictw - Kocel, Janusz; Kwiecień, Ryszard (Leśne Prace Badawcze, 2010)
The paper presents a method of determining the effects of managing natural, human and economic resources in forest districts. A synthetic indicator of management effects in forest districts has been developed, using the preference analysis, as well as the ranking and point method. The synthetic indicator consists of 18 partial indicators falling into three groups: I – indicators of utilization of nature-forest resources in a forest district, II – indicators of human resource management, III – indicators of a forest district’s economic and financial evaluation. The findings may serve the monitoring, controlling and evaluation of improvement of forest districts’ management results. The presented method is the first of the kind in the area of forestry economics in Polish and foreign literature.